Improving reading skills by encouraging children to read: A randomized evaluation of the Sa Aklat Sisikat Reading Program in the Philippines - Ama Baafra Abeberese; Todd J. Kumler; Leigh L. Linden (Institute for the Study of Labor (IZA), 2011)
We evaluate a program that aims to improve children's reading skills by providing classes with age-appropriate reading material and incentivizing children to read through a 31 day read-a-thon. During the read-a-thon, the program significantly increases the propensity of children to read, causing 20 percent more children to have read a book in the last week at school and increasing the number of books read by 2.3 in the last week and 7.2 in the last month. These increases extend both after the end of the program and outside of school, although at lower rates. The program also increased students' scores on a reading assessment, causing students' scores to improve by 0.13 standard deviations immediately after the program. The effect persisted even after the program ended with an effect of 0.06 standard deviations three months later.
urn:nbn:de:101:1-201107042618
Keywords: I21; I28; O15; 330; education; reading; development